Văn học Việt Nam thế kỷ XX : Truyện ngắn 1945-1975. Q.2, T.7 - Phan Cự Đệ; Bùi Việt Thắng; Hà Văn Đức; Lý Hoài Thu; Hồ Thu Giang; Nguyễn Thị Hương Giang (Hà Nội : Văn học, 2004)
Nguyên Hồng; Bùi Hiển; Tô Hoài; Nguyễn Trọng Hứa; Băng Hồ; Hải Hồ; Trang Thế Hy; Lê Vĩnh Hoà; Trần Ninh Hồ; Tô Ngọc Hiến.
Keywords: Văn học Việt; Truyện ngắn Việt, -- 1945-1975.